Impact of tourism activity on urban land and housing market activity: Evidence from Croatia - Tajana Barbić (Economies, 2024)
This paper explores the interplay of tourism activity, local expenditures on environmental protection, and the decisions to purchase apartments, family houses, and urban land. A random effects panel model is estimated by using data from cities and municipalities from 2012 to 2021 in Croatia, a European economy heavily dependent on tourism. The findings suggest that increasing tourism intensity at a destination motivates apartment purchase decisions but does not influence family house purchases as significantly. Municipal environmental expenditures show a positive relationship with apartment and family house purchase decisions, suggesting that investments in environmental protection may enhance the attractiveness of urban living spaces, leading to increased demand for apartments. Finally, the results reveal that growth in urban land purchases for housing construction is linked to increased short-term rentals and higher municipal housing expenditures. This research contributes to understanding housing market behavior. The results provide actionable insights for policymakers in tourism-dependent economies, emphasizing the need to balance tourism growth with housing affordability and sustainable urban development.
Keywords: 330; tourism; urban land purchases; housing unit purchases; environmental expenditures; Croatia